Occupational therapy practice guide related to driving rehabilitation for older driver in Malaysia / Nurani Nordin, Akehsan Dahlan and Mohamad Ghazali Masuri - Nordin, Nurani; Dahlan, Akehsan; Masuri, Mohamad Ghazali (Faculty of Health Sciences, Universiti Teknologi MARA, 2025)
This practice guide is designed to provide a structured framework for occupational therapists in Malaysia to evaluate and address older adults' driving abilities which aimed to promote safe mobility and support successful ageing. The material is systematically developed based on evidence from the literature and consensus of expert opinions. This practice guide aimed to assist occupational therapists in their decision making and improve their capacity as occupational therapists who are practicing driving rehabilitation for older drivers. This practice guide is divided into two main parts. The first part provides a background for understanding the issues of driving in older adults and also the requirements needed for older adults in order for them to drive safely on road. Perhaps this section can provide necessary information to the practitioners to better understand important aspects of driving and older adults. Part two focusses on provision of services by occupational therapists. This includes the guideline and recommendation for occupational therapists to practice the area of driving rehabilitation in Malaysia. While aiming for the best practice for older adults' care, this practice guide may facilitate occupational therapists utilizing evidence-based information to guide their practice. This "Occupational Therapists' Practice Guide Related to Driving Rehabilitation for Older Drivers in Malaysia" is a detailed guideline that is designed to provide a comprehensive resource for occupational therapists working in the field of driving rehabilitation for older adults and promote consistent practice throughout the country.